Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T12:21:31+01:00
A) 3( 2x -1) + 5x = 2 - [ 4x- ( 1- 2x)]
6x - 3 + 5x = 2 -(4x -1 +2x)
11 x - 3 = 2 - 4x + 1 - 2x
11x - 3 = -6x + 3 /+6x i +3
17x = 6
x = 6/17




b) x ( x + 1) - ( x² + 1) < 2 ( -x + 3 )
x² + x -x² -1 < -2x + 6
x + 1 < -2x + 6 /+2x i -1
3x < 5 /:3
x < 5/3
x < 1 i 2/3
1 5 1
2010-02-16T12:24:01+01:00
A) 3( 2x -1) + 5x = 2 - [ 4x- ( 1- 2x)]=6x-3+5x=2-[4x-1+2x]=11x-3=2-4x+1-2x=
17x=5/:17
x=5/17
b) x ( x + 1) - ( x² + 1) < 2 ( -x + 3 )=x²+x-x²-1<-2x+6=x + 1 < -2x + 6 /+2x i -1
3x < 5 /3x < 5/3
x < 1 i 2/3

Ps mam nadzieje że pomogłam ;)
2010-02-16T14:48:22+01:00
A)
3( 2x -1) + 5x = 2 - [ 4x- ( 1- 2x)]
6x-3+5x=2-[4x-1+2x]
6x-3+5x=2-4x+1-2x
6x+5x+4x+2x=2+1+3
17x=6
x=6/17


b)
x ( x + 1) - ( x² + 1) < 2 ( -x + 3 )
x²+x-x²-1<-2x+6
x+2x<6+1
3x<7
x<2¹/₇